2008
DOI: 10.1002/jnr.21664
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Wallerian degeneration of cranial corticospinal tracts in cervical spinal cord injury patients using diffusion tensor imaging

Abstract: Diffusion tensor imaging (DTI) has the potential to reveal disruption of white matter microstructure in chronically injured spinal cords. We quantified fractional anisotropy (FA) and mean diffusivity (MD) to demonstrate retrograde Wallerian degeneration (WD) of cranial corticospinal tract (CST) in cervical spinal cord injury (SCI). Twenty-two patients with complete cervical SCI in the chronic stage were studied with DTI along with 13 healthy controls. Mean FA and MD values were computed for midbrain, pons, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 43 publications
6
35
0
Order By: Relevance
“…Yamamoto et al 4 observed histological evidence of retrograde degeneration after SCI in supraspinal areas reaching as high as the pons. In a study by Guleria et al, 14 alterations in DTI metrics suggesting retrograde degeneration after SCI were shown along the corticospinal tract in the medulla, pons, midbrain and PLIC. Freund et al 15 observed a reduction in the FA in patients with SCI in the pyramids and the PLIC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Yamamoto et al 4 observed histological evidence of retrograde degeneration after SCI in supraspinal areas reaching as high as the pons. In a study by Guleria et al, 14 alterations in DTI metrics suggesting retrograde degeneration after SCI were shown along the corticospinal tract in the medulla, pons, midbrain and PLIC. Freund et al 15 observed a reduction in the FA in patients with SCI in the pyramids and the PLIC.…”
Section: Discussionmentioning
confidence: 92%
“…However, these studies consisted of relatively small samples and primarily included subjects with complete SCI. 5,14,15 The purpose of this study was to quantitatively assess the state of the cerebral white matter tracts in chronic traumatic SCI using DTI in a generalizable sample of patients with both clinically complete and incomplete SCI. We also investigated the association of DTI values with clinical neurological deficit.…”
Section: Introductionmentioning
confidence: 99%
“…However, the translation of this technique for use in human SCI presents many challenges, including (1) the low signal-tonoise ratio and image resolution of human spinal MRI may prevent the accurate anatomical definition of the injured tissues; (2) the more challenging respiratory motion that complicates human spinal MRI, since the spine immobilization device used in rodents is not applicable in humans; (3) the severely degraded echo planar diffusion-weighted MRI quality due to severe susceptibility effects that prevent as high-quality spinal DTI in humans compared to that of rodents within a reasonable time period; and (4) the limited time frame to perform the acute MRI before stabilizing hardware placement in SCI patients. Despite these challenges, there have been some human spinal cord DTI reports in the literature (Ellingson et al, 2008a(Ellingson et al, , 2008bFacon et al, 2005;Guleria et al, 2008;Shanmuganathan et al, 2008;Yeatman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It results in a loss of diffusion anisotropy (Batchelor, Atkinson et al 2003) and is reported in the cranial CST after cervical SCI (Guleria, Gupta et al 2008). …”
Section: Lumbar Enlargement (Le)mentioning
confidence: 95%